Keynes, Kuhn and the sociology of knowledge: a comment on Pernecky and Wojick. (30th June 2020) - Thomas, Rod
Abstract: Mark Pernecky and Paul Wojick use T.S. Kuhn's philosophy of science to diagnose The problematic nature and consequences of the effort to force Keynes into the conceptual cul-de-sac of Walrasian economics . But their diagnosis is itself problematical in nature and consequence. It assumes the virtues of a pre-Kuhnian philosophy of knowledge that the Kuhnian meta-framework overtly discards. One way to eliminate the inconsistency is to recognise that Kuhn's philosophy of science and sociology of knowledge function to immunise theories from criticism. Anyone who wishes to embrace a sociologically more critical philosophy ought to consider instead the philosophical attitude of critical rationalism.